Thin-wall vacuum decay in the presence of a compact dimension - Ignatios Antoniadis; Daniele Bielli; Auttakit Chatrabhuti; Hiroshi Isono (Journal of High Energy Physics)
Abstract We study the problem of false vacuum decay in arbitrary dimensions, in the presence of gravity, and compute the transition probability within the thin-wall approximation, generalising the results of Coleman and de Luccia. In the particular case of one compact dimension, we present explicit formulae for the Euclidean Bounce configuration that drives the transition from a de Sitter to Minkowski or from a Minkowski to anti-de Sitter vacua.